Sexual Harassment through Social Media Review from Electronic Transaction Information Law (Universitas PGRI Madiun, 2022)
The purpose of this study is to find out: first, the modus operandi of the perpetrator in committing sexual harassment on social media. Second, to find out the formulation of the offense in Article 27 paragraph (1) of Law Number 19 of 2016 concerning amendments to Law Number 11 of 2008 concerning Electronic Transaction Information (ITE) reaching out to forms of sexual harassment on social media. The research uses normative research with a statutory approach. The results of the study conclude, First, there are at least 3 (three) modus operandi in general: a) by sending text or images with negative content to the victim; b) spamming or writing inappropriate comments in the victim's comment field or social media; c) by approaching the opposite sex who is the target (victim). Approaching the opposite sex who is being targeted is generally accompanied by threats or rewards. Second, in relation to Article 27 paragraph (1) of the ITE Law, it cannot reach various forms of sexual harassment through social media and prevent the birth of new forms of similar crimes through social media. This is because these provisions do not meet the elements of lex certa and lex scripta, namely that a law must contain elements of both actions, conditions and consequences. In addition, a law must be strict, firm, clear and not contain various interpretations